2016
DOI: 10.1175/jcli-d-15-0695.1
|View full text |Cite
|
Sign up to set email alerts
|

Will a Warmer World Mean a Wetter or Drier Australian Monsoon?

Abstract: Multimodel mean projections of the Australian summer monsoon show little change in precipitation in a future warmer climate, even under the highest emission scenario. However, there is large uncertainty in this projection, with model projections ranging from around a 40% increase to a 40% decrease in summer monsoon precipitation. To understand the source of this model uncertainty, a set of 33 climate models from the Coupled Model Intercomparison Project phase 5 (CMIP5) is divided into groups based on their fut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
66
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(69 citation statements)
references
References 49 publications
3
66
0
Order By: Relevance
“…when associated with 10 a decrease of the intensity of the moist flow during the monsoon period. The differences between our study and the one of Trenberth et al (2005) are consistent with the theory that precipitation over western and northern Australia (the part of Australia mostly influenced by the monsoon flow in DJF) are strongly sensitive to the SST over the western central Pacific Ocean (10°S-10°N; 150°-200°E) (Brown et al, 2016). In ERA-Interim and Wang et al (2016), during 1995-2010, the SST over this part of ocean has increased (indicated by a moistening, according to C-C law), and is associated with a drying over 15 Australia, while during 1988-2001, a strong drying is observed over the central western Pacific Ocean, associated with a moistening over Australia.…”
Section: Trends In Gps and Era-interim Iwv (1995-2010) 20supporting
confidence: 91%
“…when associated with 10 a decrease of the intensity of the moist flow during the monsoon period. The differences between our study and the one of Trenberth et al (2005) are consistent with the theory that precipitation over western and northern Australia (the part of Australia mostly influenced by the monsoon flow in DJF) are strongly sensitive to the SST over the western central Pacific Ocean (10°S-10°N; 150°-200°E) (Brown et al, 2016). In ERA-Interim and Wang et al (2016), during 1995-2010, the SST over this part of ocean has increased (indicated by a moistening, according to C-C law), and is associated with a drying over 15 Australia, while during 1988-2001, a strong drying is observed over the central western Pacific Ocean, associated with a moistening over Australia.…”
Section: Trends In Gps and Era-interim Iwv (1995-2010) 20supporting
confidence: 91%
“…Several models project very large increases or decreases in total rainfall. Model 14 projects the largest decrease (−42%) which has been noted previously to be related to warming in the western equatorial Pacific where the model also has a large negative sea surface temperature bias (Brown et al ., ). The present analysis finds that this decrease is associated with a decrease in the percentage of rain that falls on burst days (−48%, Figure b), a decrease in burst days (−58%, Figure c) and a large decrease (−42%) in the number of burst events (Figure d).…”
Section: Results From Cmip5 Modelsmentioning
confidence: 98%
“…The station data analysed here are for Darwin Airport (WMO Station 94120) while the regional average values (that encompass Darwin) refer to the “Australian monsoon domain” defined here by (land areas within) 10–20 ° S, 110–150 ° E for both observations and models, consistent with previous studies, for example, Brown et al . (). The Australian monsoon domain and Darwin locations are shown in Figure .…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, this Tripole index is a relevant tool to monitor future SST warming in the near future, and in future projection work and how it may impact on future SEA rainfall trends. The spatial pattern of SST warming in the tropical Pacific was also found to be an important influence on northern Australian rainfall projections (Brown et al ., ). It confirms the importance of patterns of tropical warming in driving range of rainfall projections across Australia from climate models as was noted by Watterson () for the CMIP3 generation of models.…”
Section: Discussionmentioning
confidence: 97%